Descripcion de la larva de Brachyleptura strangulata Germar, 1824: (Coleoptera, Cerambycidae) - Iglesias, C.=700 1 De Viedma, M.G.; Notario, A.; Baragaño, J.R.
(Es, En)
ilus., 6 ref.
Keywords: COLEOPTERA; CERAMBYCIDAE; INSECTA; LARVAS; PINUS; TOCON; IDENTIFICACION; ESPAÑA